A hoard of Celtic and Roman coins from the Ljubljanica River A contribution to the chronology of the coinage of the Taurisci - Kos, Peter; Šemrov, Andrej (Arheološki vestnik, 2003)
The find of 59 large and small Celtic coins and 23 Romanrepublican coins is exceptionally interesting and important,as it is one of the few found in the broader region of the easternAlps where Celtic coins from two different areas were foundtogether with Roman coinage. The find therefore enables anentirely objective verification of the accuracy of the dating forthe minting of coins by the Norici and the Taurisci. The findfrom the Ljubljanica represents essential proof that the tribeof the Taurisci minted its own coinage as early as the middleof the 2nd century BC (similarly as the tribe of the Norici onthe northern side of the Karavanke Mountains).